A note on flow behavior in axially-dispersed plug flow reactors with step input of tracer. (January 2019) - Huang, Yuanlong; Seinfeld, John H.
Abstract: Atmospheric chemistry studies are frequently conducted in flow reactors, such as the potential aerosol mass (PAM) reactor. To characterize the flow condition in such a reactor, an axially-dispersed plug flow reactor (AD-PFR) model has been applied to explain the observed residence time distribution (RTD). Compared with the traditional RTD analysis that directly fits the observed data from a pulse input or differentiates the data points from a step input, we introduce here a direct method to retrieve the axial diffusivity in an AD-PFR model by fitting an analytical formula to the rising profile of the tracer at the beginning of the experiment (the transition data before the reactor reaches steady state). This method can be readily used to determine the flow conditions inside an AD-PFR. Highlights: Cumulative RTD can be used to characterize flow conditions in flow reactors. Step injection is recommended to measure cumulative RTD. Derivation of the analytical expression of cumulative RTD in AD-PFR model.